Evaluating Point-of-Care Nucleic Acid Tests in Adult Human Immunodeficiency Virus Diagnostic Strategies: A Côte d'Ivoire Modeling Analysis. (13th May 2021) - Neilan, Anne M; Cohn, Jennifer; Sacks, Emma; Gandhi, Aditya R; Fassinou, Patricia; Walensky, Rochelle P; Kouadio, Marc N; Freedberg, Kenneth A; Ciaranello, Andrea L
Abstract: Background: The World Health Organization (WHO) human immunodeficiency virus (HIV) diagnostic strategy requires 6 rapid diagnostic tests (RDTs). Point-of-care nucleic acid tests (POC NATs) are costlier, less sensitive, but more specific than RDTs. Methods: We simulated a 1-time screening process in Côte d'Ivoire (CI; undiagnosed prevalence: 1.8%), comparing WHO- and CI-recommended RDT-based strategies (RDT-WHO, RDT-CI) and an alternative: POC NAT to resolve RDT discordancy (NAT-Resolve). Costs included assays (RDT: $1.47; POC NAT: $27.92), antiretroviral therapy ($6–$22/month), and HIV care ($27–$38/month). We modeled 2 sensitivity/specificity scenarios: high-performing (RDT: 99.9%/99.1%; POC NAT: 95.0%/100.0%) and low-performing (RDT: 91.1%/82.9%; POC NAT: 93.3%/99.5%). Outcomes included true-positive (TP), false-positive (FP), true-negative (TN), or false-negative (FN) results; life expectancy; costs; and incremental cost-effectiveness ratios (ICERs: $/year of life saved [YLS]; threshold ≤$1720/YLS [per-capita gross domestic product]). Results: Model-projected impacts of misdiagnoses were 4.4 years lost (FN vs TP; range, 3.0–13.0 years) and a $5800 lifetime cost increase (FP vs TN; range, $590–$14 680). In the high-performing scenario, misdiagnoses/10 000 000 tested were lowest for NAT-Resolve vs RDT-based strategies (FN: 409 vs 413–429; FP: 14 vs 21–28). Strategies had similar life expectancy (228 months) and lifetime costs ($220/person) among all tested; ICERs were $3450/YLS (RDT-CI vs RDT-WHO) and $120 910/YLS (NAT-Resolve vs RDT-CI). In the low-performing scenario, misdiagnoses were higher (FN: 22 845–30 357; FP: 83 724–112 702) and NAT-Resolve was cost-saving. Conclusions: We projected substantial clinical and economic impacts of misdiagnoses. Using POC NAT to resolve RDT discordancy generated the fewest misdiagnoses and was not cost-effective in high-performing scenarios, but may be an important adjunct to existing RDT-based strategies in low-performing scenarios.